Secondary prevention of osteoporosis and osteoporotic fractures in real clinical practice and possibilities of its improvement with strontium ranelate - Nataliya Vladimirovna Toroptsova (Современная ревматология, 2012)
The main ultimate goal of secondary prevention of osteoporosis (OP) is to reduce the risk of fracture in patients with the already existing disease; the effect of pathogenetic agents develops only if they are used regularly and long. Low patient adherence to treatment minimizes all efforts to prevent OP complications. There is low-frequency prescription of pathogenetic antiosteoporotic agents to this category of patients. There is a wide range of pathogenetic antiosteoporotic drugs today. On choosing a medicine, a physician should rely on its proven efficacy and safety, as well as its convenience use for a specific patient. The data of an international clinical trial to prevent fractures during long-term therapy with strontium ranelate are given.